2019
DOI: 10.2478/biolet-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

In vitro interactions between Trichoderma harzianum and pathogenic fungi damaging horse-chestnut (Aesculus hippocastanum) leaves and fruits

Abstract: Interactions between 3 pathogenic fungi damaging horse-chestnut (Aesculus hippocastanum) leaves and fruits -Phyllosticta sphaeropsoidea, Phomopsis carposchiza, and Diaporthe padi -and the antagonistic fungus Trichoderma harzianum were studied to determine their mutual influence in vitro. Antibiosis of colonies developing on 5 nutrient media was tested. The 3 studied T. harzianum isolates differed in their antagonistic potential. although T. harzianum isolates significantly inhibited the growth of Phomopsis car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…In contrast, T. viride (Tv8) had the lowest inhibition percent for all pathogenic strains. Similar results were previously recorded by [15] in a study which tested T. harzianum against three pathogenic fungi (Phyllosticta sphaeropsoidea, Phomopsis carposchiza, and Diaporthe padi) and found an inhibition percentage of up to 20%. Other previous work [86], tested two Trichoderma strains against 18 Botrytis cinerea strains and found that the mycelial growth inhibition from 74.2% to 96.9% and from 71.1% to 95.9% for T. asperellum and T. harzianum, respectively.…”
Section: Ability To Antagonize Soil-borne Pathogenic Fungisupporting
confidence: 89%
See 2 more Smart Citations
“…In contrast, T. viride (Tv8) had the lowest inhibition percent for all pathogenic strains. Similar results were previously recorded by [15] in a study which tested T. harzianum against three pathogenic fungi (Phyllosticta sphaeropsoidea, Phomopsis carposchiza, and Diaporthe padi) and found an inhibition percentage of up to 20%. Other previous work [86], tested two Trichoderma strains against 18 Botrytis cinerea strains and found that the mycelial growth inhibition from 74.2% to 96.9% and from 71.1% to 95.9% for T. asperellum and T. harzianum, respectively.…”
Section: Ability To Antagonize Soil-borne Pathogenic Fungisupporting
confidence: 89%
“…At 25 ºC on PDA, Ta1 and Tv8 had the highest and lowest growth rates, respectively, and on CMD, Th6 and Th4 had the highest and lowest growth rates, respectively. Several studies have claimed that potato dextrose medium is the best choice for the growth of Trichoderma fungi [6,14,15,72]. One study [73] evaluated the growth of T. harzianum on five culture media namely, PDA, modified potato dextrose agar, water agar (WA), carrot agar (CA) and cornmeal agar (CMA), PDA and WA were found to be more and less effective for growth, respectively.…”
Section: Growth Under Thermal Stress and Different Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Identified strains of bacteria B. pumilis, B. methyloprophics, Brevibacterum halotolerans, active against a fairly wide range of apple mycopathogens [2,6]. Based on the high antagonistic potential, growth rate and the possibility of cultivation under industrial conditions, fungi of the genus Trichoderma are widely used [12][13][14]. However, most of the drugs created in Russia are registered for use on cereals, vegetables, industrial crops [6], while for the control of apple diseases -only 5.…”
Section: Introductionmentioning
confidence: 99%
“…MARTÍNEZ-COCA et al, 2013;BHAT, 2017;RAMARAJU et al, 2017;RONNIE- GAKEGNE and MARTÍNEZ-COCA, 2018;ALFIKY, 2019;PASTIRČÁKOVÁ, 2019).The majority of fungal biopesticides are formulated based on infectious propagules obtained from different fermentation systems. However, they can also exert their action from biomass and currently they are developing fungal biopesticides based on proteins, secondary metabolites, enzymes and RNA interference(GHORBANPOUR et al, 2017;BAUTISTA et al, 2018).…”
mentioning
confidence: 99%